Konsepsi Persepsi Manfaat Dalam Keterlibatan Konsumen Terhadap Kebaruan Produk - Ignasius Heri Satrya Wangsa; Maria Josephine Tyra (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2021)
The competitive business environment demands innovative efforts to create product newness. Within consumer-oriented goals, the business should create arecognizable product newness. Consumption in economic rationality is theconsumption of benefits. Therefore, recognizable product newness occurs when the product itself is perceived to be beneficial. This research resulted in two basicconcepts of perceived-benefit of product newness through consumer involvement, namely experienced-driven benefit and economically rationalized benefit. This research is expected to contribute to the theories of perceived benefit, consumer involvement, and product newness.